Temporomandibular Disorders: Fundamental Questions and Answers - (:unkn) unknown (AVES, 2020)
This review aimed to present the current evidence-based answers to a questionnaire which was developed to evaluate the beliefs and knowledge of dental professionals concerning temporomandibular disorder (TMD). A literature review was conducted using the PubMed/Medical Literature Analysis and Retrieval System Online (MEDLINE), Cochrane, Google Scholar, and Scopus search engines from January 1980 to June 2020 corresponding to TMD diagnosis, causes, management, and consequences. A total of 50 articles were considered relevant and selected for full review. The etiology of TMD is multifactorial and complicated and involves several direct and indirect factors. Orthodontic treatment does not appear to either prevent or relieve TMD to a great degree. Nevertheless, condylar and occlusal stability reduces the risk of TMD development. As a result, an assessment of the function of masticatory system prior to beginning orthodontic therapy is fundamental. If signs and symptoms of TMD are significantly present, they should be managed before any orthodontic intervention. Moreover, psychological disorders are strongly associated with joint and facial pain. Thus, professionals who work with chronic TMD patients need to be aware of the psychological aspects of chronic pain and refer the patient for psychological evaluation when warranted. Future research elucidating a cause- effect relationship and neurobehavioral processes underlining chronic pain should be performed.
Keywords: Diagnosis; etiology; questionnaire; temporomandibular disorder; treatment; OCCLUSAL INTERFERENCES; FOLLOW-UP; JOINT; PAIN; DYSFUNCTION; MANAGEMENT; KNOWLEDGE; THERAPY; TMD; ORTHODONTICS